Pengaruh sosialisasi pajak dan layanan Instansi terhadap kepatuhan wajib pajak Pajak Bumi dan Bangunan perkotaan dan pedesaan - Reaksi Zagoto; Erasma Fitilai Zalogo (University of Merdeka Malang, 2023)
This research was conducted to determine the effect of tax socialization and service quality on the compliance of land and building tax-P2 taxpayers in the village of Sisarahili Oyo, Onohazumba District. The population in this study were all village communities totaling 780 people. The sample was determined as many as 101 people using quota sampling. The data analysis method used is multiple linear regression. Hypothesis testing is carried out partially by using the t test and simultaneous or simultaneous tests using the F test. all data analysis processes use the SPSS 22 application. Based on the results of the study, the authors conclude that partially there is no effect of Tax Socialization on Tax Compliance, and partially Agency Services have a positive influence on Tax Compliance. The results of the simultaneous test of socialization and agency services variables have a positive influence on tax compliance. To increase Compliance of Urban and Rural Land and Building Taxpayers, related agencies need to provide Agency Services with due regard to physical evidence (tangibles), Reliability. and Empathy.